IMPLEMENTATION OF PURCHASE ADMINISTRATION TO MEET THE INVENTORY OF LIGHT STEEL GOODS AND METAL ROOFS AT PT ADDESIA JAYA SEJAHTERA JAKARTA - Yulia Mujiaty; Deasy Novayanti; Darma Wijaya; Siti Nurjanah; Nur Arifah (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
An important component in the company's procurement process is purchase. Starting from which supplier to buy, the type and quantity of goods to be purchased, and when to complete the purchase process. The purchasing department often prioritizes the selection of suppliers with the most affordable (lowest) prices and high-quality products. The purpose of purchasing a product is to guarantee its availability for use in the sales process, which highlights how important it is to purchase the product to meet a company's need for the product and keep costs low. In this study, the author uses a qualitative research methodology. To describe and study the phenomena, events, social activities, attitudes, beliefs, perceptions, and thoughts of people individually and in groups, qualitative research is used. Implementation of procedures to meet the inventory of merchandise Purchase Order (PO) Achievement of Sales of Metal Mesh and Roof Products Achievement of Purchase of Light Steel Products and Metal Roofs Obstacles faced when making purchases and how to overcome them Procedures for purchasing goods in the purchasing department of PT. Addesia Jaya Sejahtera is quite good, but it still has some shortcomings for the process of purchasing goods, such as recording transactions twice so that it takes a short time, price changes without confirmation and approval processes that take a long time and sometimes lack accuracy from purchasing when ordering goods